Clinical and Radiological Outcomes in Patients With Anterior Shoulder Instability and Glenoid Bone Loss after Arthroscopic Free Bone Block Combined With Dynamic Anterior Stabilization. Issue 1 (January 2023) - Wu, Chenliang; Xu, Junjie; Fang, Zhaoyi; Chen, Jiebo; Ye, Zipeng; Wu, Xiulin; Li, Ziyun; Wang, Liren; Kang, Yuhao; Zhao, Song; Xu, Caiqi; Zhao, Jinzhong
Background: As an alternative to the Latarjet procedure, the arthroscopic free bone block (FBB) procedure combined with dynamic anterior stabilization (DAS) has been recently proposed to provide both glenoid augmentation and a tendon sling effect for treating anterior shoulder instability (ASI) with glenoid bone loss. Purpose: To evaluate the clinical and radiological outcomes of FBB-DAS for ASI with glenoid bone loss. Study Design: Case series; Level of evidence, 4. Methods: Patients who underwent arthroscopic FBB-DAS for ASI with >15% glenoid bone loss between February 2017 and March 2020 were screened and enrolled in this study. Clinical outcome measures were assessed preoperatively and at a minimum 2-year follow-up, including recurrence, complications, shoulder functional scores, range of motion, and return to sports. Postoperative computed tomography and magnetic resonance imaging were also performed. Results: Of a total of 65 patients with a mean follow-up of 46.1 ± 13.1 months, no patients experienced a recurrent dislocation or subluxation postoperatively, while 2 had a positive anterior apprehension test (3.1%). Additionally, 2 patients (3.1%) experienced complications of hematoma and shoulder stiffness, respectively. The mean visual analog scale score, American Shoulder and Elbow Surgeons score, Rowe score, and Oxford Shoulder Instability Score all improved significantly from 3.2 ± 2.4, 75.0 ± 18.9, 43.6 ± 27.3, and 33.8 ± 9.0 preoperatively to 1.3 ± 0.8, 95.1 ± 8.0, 95.5 ± 7.8, and 14.8 ± 3.5 at final follow-up, respectively (all P < .001). No difference was detected in range of motion except for 8.1° and 7.5° external rotation limitations in adduction and abduction, respectively. There were 62 patients (95.4%) who returned to sports, and 54 patients (83.1%) returned to the preinjury level. The transferred biceps tendon was intact in all 59 patients who completed radiological examination at the latest follow-up. Good bone healing was achieved in 98.3% of patients, and the glenoid bone defect decreased from 18.1% to 4.9%. Osseous and labral glenoids were significantly enlarged in width and depth on the latest magnetic resonance imaging (all P < .001). Conclusion: Arthroscopic FBB-DAS provided satisfactory clinical and radiological outcomes for ASI with glenoid bone loss. Despite slight external rotation restrictions, it achieved low recurrence and complication rates, excellent shoulder functional scores, a high return-to-sports rate, and favorable graft healing and remodeling.